2016
DOI: 10.1021/acs.biochem.6b00085
|View full text |Cite
|
Sign up to set email alerts
|

Synaptotagmin I’s Intrinsically Disordered Region Interacts with Synaptic Vesicle Lipids and Exerts Allosteric Control over C2A

Abstract: Synaptotagmin I (Syt I) is a vesicle-localized integral membrane protein that senses the calcium ion (Ca(2+)) influx to trigger fast synchronous release of neurotransmitter. How the cytosolic domains of Syt I allosterically communicate to propagate the Ca(2+) binding signal throughout the protein is not well understood. In particular, it is unclear whether the intrinsically disordered region (IDR) between Syt I's transmembrane helix and first C2 domain (C2A) plays an important role in allosteric modulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Aside from the C2 domains, synaptotagmins exhibit substantial variation in amino acid sequence in the region between the transmembrane domain and the C2A domain. In Syt-1, the N- and C-terminal portions of this linker region are rich in basic and acidic residues, respectively, and have been suggested to comprise an electrostatic zipper that contributes to regulation of fusion pore opening and protein–lipid binding ( Lai et al, 2013 ; Lu et al, 2014 ; Fealey et al, 2016 ). The sequence of the canonical Syt-7 linker region displays a somewhat similar electrostatic pattern, although the overall sequence conservation is low ( Fig.…”
Section: Structural and Biochemical Properties Of Syt-7mentioning
confidence: 99%
“…Aside from the C2 domains, synaptotagmins exhibit substantial variation in amino acid sequence in the region between the transmembrane domain and the C2A domain. In Syt-1, the N- and C-terminal portions of this linker region are rich in basic and acidic residues, respectively, and have been suggested to comprise an electrostatic zipper that contributes to regulation of fusion pore opening and protein–lipid binding ( Lai et al, 2013 ; Lu et al, 2014 ; Fealey et al, 2016 ). The sequence of the canonical Syt-7 linker region displays a somewhat similar electrostatic pattern, although the overall sequence conservation is low ( Fig.…”
Section: Structural and Biochemical Properties Of Syt-7mentioning
confidence: 99%
“…The underlying mechanisms by which Syt 1 mediates this biological event remain incompletely understood. Our goal has been to investigate the allosteric network of Syt 1 to elucidate regulatory mechanisms that underlie controlled neurotransmitter release (2)(3)(4). Our group found that an intrinsically disordered region (IDR) within Syt 1 (residues $80-141) exerts allosteric influence over the adjacent C2 domain referred to as ''C2A'' ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Our group found that an intrinsically disordered region (IDR) within Syt 1 (residues $80-141) exerts allosteric influence over the adjacent C2 domain referred to as ''C2A'' ( Fig. 1 A) (4). Until recently, this IDR had received little attention and its structural biology still represents a significant gap in our understanding of Syt 1 function.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group provided evidence in support of such a mechanism. 4 We found that the IDR of Syt-1 is structurally sensitive to the lipid composition of the membrane, undergoing pronounced changes upon association. While the IDR seems to be mostly disordered when associated with a membrane whose lipid composition mimics that of a synaptic vesicle, its interaction still has a profound impact on the adjacent C2 domain (C2A).…”
mentioning
confidence: 75%